Tantangan dan Peluang: Inovasi dalam Kurikulum Merdeka bagi Guru Madrasah Ibtidaiyah di Trangkil - Af'idah, Irma Nur; Nisfa, Nia Lailin; Putri, Farah Kamelia Ali; Afrida, Fira Nadliratul; Muhaiminan, Hazib Maulana Amril (Kifah: Jurnal Pengabdian Masyarakat, 2024)
The curriculum merdeka has been implemented simultaneously in the 2023/2024 academic year. At the Elementary School and Madrasah Ibtidaiyah levels, it has been implemented in grades I and IV. This service aims to provide a deeper understanding of the implementation of the independent curriculum regarding initial assessment, differentiated learning, preparation of teaching modules and preparation of P5P2RA modules. The implementation methods used are observation, coordination with partners, outreach, implementation of activities and program evaluation. The intended target is MI teachers in Trangkil District. The results obtained from this service are that teachers are able to understand in more depth how to implement the independent curriculum concept according to the characteristics and needs of students. Apart from that, teachers know the differentiated learning process in accordance with the concept of teaching at the right level.